Engaging with Scale and Place: Geographical Thinking on Migration in Middle-School - Sandahl, Johan (Journal of Geography Education, 2023)
This article addresses the challenges of teaching migration as a complex content in middle-school geography education. In this collaborative educational design research project between a researcher and teacher in Sweden, students engaged with data and different types of knowledge to develop powerful geographical knowledge. The article provides empirical examples of powerful geographical knowledge through descriptions of how middle-school students’ (12-year-olds) understandings of migration changed through teaching. The article highlights students’ preconceptions about migration and describes the teaching intervention with contextual content, and substantive and procedural concepts. It also addresses how students’ reasoning developed after the teaching.